Clinically important change on the Unified Dyskinesia Rating Scale among patients with Parkinson's disease experiencing dyskinesia - Pahwa, Rajesh; Fox, Susan; Hauser, Robert A.; Isaacson, Stuart; Lytle, Judy; Johnson, Reed; Llorens, Lily; Formella, Andrea E.; Tanner, Caroline M. (Frontiers in Neurology, 2022)
Background The Unified Dyskinesia Rating Scale (UDysRS) evaluates dyskinesia in patients with Parkinson's disease (PD). A minimal clinically important change (MCIC)—the smallest change in a treatment outcome that a patient considers important—remains undefined for the UDysRS. Objective To utilize pivotal amantadine delayed-release/extended-release (DR/ER) trial data to derive MCICs for the UDysRS total score in patients with PD experiencing dyskinesia. Methods Pivotal trials included PD patients with ≥1 h daily ON time with troublesome dyskinesia and baseline scores ≥2 on the Movement Disorder Society-Unified Parkinson's Disease Rating Scale (MDS-UPDRS) Part IV, item 4.2. Patients randomized to amantadine DR/ER or placebo completed two consecutive 24-h diaries before each clinic visit and were evaluated during ON time with dyskinesia using the UDysRS, MDS-UPDRS, and Clinician Global Impression of Change (CGI-C). The UDysRS changes from baseline to week 12 were anchored to corresponding changes in MDS-UPDRS item 4.2 scores. A minimal clinically important improvement in the CGI-C and diary-reported ON time with troublesome dyskinesia (≥0.5 h) were supportive anchors. Receiver operating characteristic curves determined the UDysRS change values optimizing sensitivity and specificity to at least minimal improvement on each anchor. Results The analyses included 196 patients. Week 12 UDysRS total score reduction of ≥8 points corresponded to at least minimal MDS-UPDRS item 4.2 improvement. UDysRS reduction of ≥9 points corresponded to decreased ON time with troublesome dyskinesia of ≥0.5 h per patient diaries, and UDysRS reduction of ≥10 points corresponded to at least minimal improvement on the CGI-C. Conclusion Anchored to the MDS-UPDRS Part IV, item 4.2, an 8-point reduction in the UDysRS total score can be considered an MCIC for PD patients with dyskinesia.